Concrete Ways to Decolonize Research - Asselin, Hugo; Basile, Suzie (An International Journal of Critical Geographies, 2018)
« Almost 20 years after Māori scholar Linda Tuhiwai Smith’s call to decolonize research (Smith, 1999), significant progress has been made into drafting ethics principles to guide research with Indigenous people (e.g., CIHR et al., 2014). However, transforming principles into actual practices is easier said than done. It is increasingly recognizedthat “knowing the key guiding principles for research with Indigenous peoples is not always enough and [principles need to be]translated into day-to-day research practices”(Morton Ninomiya and Pollock, 2017, p. 29). This themed issue presents studies on various topics conducted in different geographical and cultural settings and suggesting concrete ways to decolonize research. The call for papers was issued following the 3rd Seminar on the ethics of research with Aboriginal people held at the Université du Québec en Abitibi-Témiscamingue in late 2014. Two previous editions of the seminar (in 2009 and 2011) had invitedparticipants2to share experiences of good and bad research practices, summarized in Asselin and Basile (2012). The 3rd seminar took a step further in focusing on concrete ways to decolonize research.In what follows, we discuss research decolonization and summarize the key messages from the keynote speakers of the 3rd seminar, some of which have contributed papers to this themed issue. Additional contributions widened the geographical scope considered (Canada, Mexico, Peru) in addition to providingmore examples of concrete ways to decolonize research. » [Extrait original p. 643-644|
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; autochtones; canada; décolonialisme; justice sociale; orpcc; outils; pour des recherches en milieux de pratiques; premiers peuples; périodes historiques; recherche en milieux de pratique; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions